2018
DOI: 10.3892/etm.2018.7104
|View full text |Cite|
|
Sign up to set email alerts
|

Allicin suppresses the migration and invasion in cervical cancer cells mainly by inhibiting NRF2

Abstract: Emerging evidence has demonstrated the antitumor activity of allicin in various tumors. However, little study has been carried out on the functional role of allicin in cervical cancer. Our data showed that allicin suppressed cervical cancer cell viability in a time- and dose-dependent manner. Allicin treatment could reverse H2O2-induced reactive oxygen species accumulation. Meanwhile, levels of glutathione and superoxide dismutase were increased, but malondialdehyde was decreased after allicin incubation for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…By inhibiting the microtubule polymerization, allicin inhibited cell polarization and migration, and reduced cell division [45,46]. Its antiproliferative activity was increased in a dose-dependent manner against human cervical cancer cells [20], cholangiocarcinoma [15], lung adenocarcinoma [44] renal cell carcinoma [47], and ovarian cancer cells [48]. Furthermore, allicin acts as a good inhibitor of colony formation, as well as cell migration [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By inhibiting the microtubule polymerization, allicin inhibited cell polarization and migration, and reduced cell division [45,46]. Its antiproliferative activity was increased in a dose-dependent manner against human cervical cancer cells [20], cholangiocarcinoma [15], lung adenocarcinoma [44] renal cell carcinoma [47], and ovarian cancer cells [48]. Furthermore, allicin acts as a good inhibitor of colony formation, as well as cell migration [15].…”
Section: Discussionmentioning
confidence: 99%
“…After washing with TBST, the membranes were incubated with secondary antibodies conjugated with horseradish peroxidase. The signals were detected after adding the chemiluminescence substrate (Invitrogen, Carlsbad, CA, USA) [8,20].…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, having an anti-NF-jB therapeutic modality might result into unwanted effects. Nrf2 is responsible for migration and invasion in cancers of the cervix [406], and aggressiveness in various cancers, such as breast cancer [407,408], gastric cancer [409] and colorectal cancer [410], or responsible for drug resistance in glioma and melanoma [411].…”
Section: Caffeic Acid Phenethyl Ester (Cape)mentioning
confidence: 99%
“…Allicin (diallyl thiosulfonate) is a versatile sulfur‐containing organic compound, which is an important lipid‐soluble active ingredient extracted from garlic ( Allium sativum L.). Studies reported that allicin has anti‐inflammatory, bactericidal, antioxidative stress, immunemodulation, neuroprotective, and antitumor effects (Borlinghaus, Albrecht, Gruhlke, Nwachukwu, & Slusarenko, 2014; Haghi, Azimi, & Rahimi, 2017; Hirsch et al., 2000; Li et al., 2019; Seki, Ishikawa, & Okada, 2018; Zhang & Yang., 2019; Zou et al., 2016). However, the effect and mechanism of allicin on the sensitivity of CRC radiotherapy have not been confirmed.…”
Section: Introductionmentioning
confidence: 99%